CHARACTERISTIC OF RARE EARTH ELEMENT IN SEDIMENT AT COASTAL AND OFFSHORE AREA OF KUNDUR ISLAND, RIAU PROVINCE - Deny Setiady; I Wayan Lugra (Marine Geological Institute of Indonesia, 2013)
The study area is located at coastal and offshore Kundur and Adjacent Area, geographically located at coordinates of 0Âº 39'00